Penerapan Algoritma Analytical Hierarchy Process (AHP) Untuk Menentukan Pola Penindakan Lalu Lintas - Anagora, Roni; Damuri, Amat; Hendratna, Gempa; Syah Putra, Arman (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
The background of this research is to make intelligent actions that can be applied to crack down on the highway, with smart measures, the human side can be eliminated and all can be done with the system, so it will eliminate the mistakes that can be made by humans. The method used by reading a lot of journals as a basis for research, with a lot of reading will deepen the research topic in search, reading can also add knowledge and can find new problems that can be raised in a study. By using the system, it will make it easier for the police to supervise and act on traffic violations on the highway, the lack of police personnel in DKI Jakarta is one of the problems that results in lack of supervision and action and can only conduct raids at any time, Application of Analytical Hierarchy Process Algorithm (AHP) And Decision Tree by making a system will greatly help the police. In this study, the authors make a proposed action system that can be used to carry out traffic control on the road by applying the Analytical Hierarchy Process (AHP) and Decision Tree Algorithm, by making a system of personnel shortages problem can be solved and in the future the police only do direct action if the problem is already serious and requires police personnel at the scene.